THEORETICAL ASPECTS OF THE ORGANIZATION BRAND MANAGEMENT - Oksana Kononenko (Сучасний стан наукових досліджень та технологій в промисловості)
The subject matter of research in the article is the development of the concept of "brand", as well as modern approaches to the process of brand formation of the organization. Recent decades the concept of "brand" has become widespread. It is applied to the individual, to the enterprise, and also to government initiatives. However, in the literature there is no single point of view on the definition of this concept. The goal of the article is to analyze the existing definitions of the concept of "brand" and modern approaches to the process of brand formation of the organization. To achieve this goal, it is necessary to solve the following tasks: to collect the definitions of the concept of a brand, given by organizations, scientists, specialists, to analyze these definitions and their dynamics, to analyze the main features of strategic brand management. The system analysis method was applied to achieve the goal of the work. Results. The most well-known definitions of the concept of "brand" are given. It is shown that it can be considered from the standpoint of a company that creates goods or provides services under its own brand, or from the standpoint of a buyer who perceives this brand. The way this concept evolves over time is analyzed. It is shown that the brands are a combination of tangible and intangible elements that can be combined into the following groups: visual design elements, distinctive product features (quality, individuality, sounds, aroma, taste, etc.), intangible aspects of customer interaction with the product or company. quality of customer service, etc.). Based on the analysis of existing concepts, the own definition of the concept of "brand" is proposed, which meets the requirements of modernity. The definition of "branding" is considered. It is shown that brand management uses a variety of marketing tools and techniques to increase the value of branded goods in the eyes of buyers and that a large proportion of buyers are willing to pay more for the product of your favorite brand. The main stages of strategic brand management include: determining the position and value of the brand, planning and implementation of the brand marketing program, measuring brand effectiveness, increasing and maintaining brand value. The concept of "brand book" and the advantages of its use are considered. The structure of the brand book is described. It is shown that it is important for the development of companies to create a marketing strategy for rebranding. In the process of rebranding, there are usually four main stages, namely: marketing audit, brand repositioning, restyling of its visual attributes and changing the principles of communication. Conclusions: the definition of "brand" and the use of strategic brand management and rebranding will form the brand of the organization, which will be better perceived by consumers and will have a positive image in society.